2022
DOI: 10.19160/e-ijer.1055195
|View full text |Cite
|
Sign up to set email alerts
|

Social Studies Teacher Candidates’ Views on Environmental Justice

Abstract: Environmental justice, which is related to the concept of social justice; It can be defined as the equal protection of everyone from harmful environmental influences, regardless of their age, culture, ethnicity, gender and race. Therefore, the right to live in a safe and healthy environment is the main emphasis of environmental justice. In addition, the participation of citizens in the decisions to be taken on environmental issues and taking into account their concerns about the environment are important aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…It is also similar to constructivist education approach and applied education regarding the education of pre-service teachers carried out by Aladejebi (2020). In addition, in the research conducted by Bursa (2022), it was concluded that applied education and sightseeing tours affect the development of environmental justice, and in the study conducted by Arisandi & Faisal (2021), collaborative and activity-based education provides significant contributions in raising ecological awareness. In addition, in the research conducted by Bursa (2022), it was concluded that applied education and sightseeing tours affect the development of environmental justice, and in the study conducted by Arisandi & Faisal (2021), collaborative and activity-based education provides significant contributions in raising ecological awareness.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also similar to constructivist education approach and applied education regarding the education of pre-service teachers carried out by Aladejebi (2020). In addition, in the research conducted by Bursa (2022), it was concluded that applied education and sightseeing tours affect the development of environmental justice, and in the study conducted by Arisandi & Faisal (2021), collaborative and activity-based education provides significant contributions in raising ecological awareness. In addition, in the research conducted by Bursa (2022), it was concluded that applied education and sightseeing tours affect the development of environmental justice, and in the study conducted by Arisandi & Faisal (2021), collaborative and activity-based education provides significant contributions in raising ecological awareness.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…When the literature on environmental education in social studies is examined, the following studies are found: Myers and Stitely's (1973) on environmental issues in social studies student materials, Adara's (1996) on environmental education strategies in social studies, Adedayo and Olawepo's (1997) on integration of environmental education into social sciences at secondary school level, Ergin's (2011) on the role of social studies in the development of environmental awareness, Karakuş, Palaz, Kılcan et al Çepni's (2012) on the use of cartoons in the teaching of environmental problems in social studies, Edinyang, Eneji, Tijani and Dunnamah's (2013) on the role of environmental education and social studies in creating an environmental-friendly society, Kodan and Bozdemir's (2014) on the contribution of science and social studies course outcomes and activities to environmental education, Öztürk and Zayimoğlu Öztürk's (2016) on the evaluation of social sciences curriculum in terms of environmental education, Fidan and Ay's (2016) on operational environmental literacy in social studies course, Çoban and Temir's (2018) on environmental education in social studies textbooks, and Apaydın Timur's (2020) on environmental education qualifications of social studies teachers, Itasanmi's (2020) on secondary school teachers' awareness and attitudes of social studies teachers towards environmental education, Iyunade & Olubela's (2020) on environmental sustainability and the relevant roles of social studies educators, Aladejebi's (2020) on environmental education in Nigerian Social Studies teacher training program, Bayram's (2021) on social studies course and environmental education, Arisandi & Faisal's (2021) on the use of cooperative learning in environmental education and its relationship with social studies, Kaya, Gökdemir and Yazıcı's (2021) on environmental education self-efficacy of social studies pre-service teachers, Bursa's (2022) on the views of social studies pre-service teachers about environmental justice. Although all these studies above were found in literature, no study has been found regarding the views of the social studies teachers on the environmental education in social sciences curriculum and textbooks.…”
Section: Introductionmentioning
confidence: 99%